PENGARUH KEMUDAHAN PENGGUNAAN TERHADAP PREFERENSI KONSUMEN DALAM MENGGUNAKAN QRIS DI TOKO BOLABARU TOYS SIDRAP - Mukarramah; Pratiwi Ramlan; Andi Riska Andreani Syafaruddin; Rahman Yakub (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital technology development has transformed public financial transaction patterns toward non-cash payment systems. One of the innovations developed by Bank Indonesia is QRIS (Quick Response Code Indonesian Standard), which facilitates payment processes through a single standardized QR code. This study aims to examine the effect of perceived ease of use on consumer preferences in using QRIS at Bolabaru Toys Store in Sidrap. Data analysis was conducted using simple linear regression to test the effect of the independent variable (ease of use) on the dependent variable (consumer preference) using SPSS 2021. The results show that ease of use has a positive and significant effect on consumer preferences in using QRIS. Based on the t-test results, the calculated t-value is greater than the t-table value and the significance value is less than 0.05, indicating that H0 is rejected and H1 is accepted. Therefore, ease of use is proven to have a significant influence on consumer preferences in using QRIS at Bolabaru Toys Store in Sidrap. The higher the level of perceived ease, the greater the likelihood that consumers will choose, reuse, and recommend QRIS as a payment method.